Treatment Outcomes in Patients Undergoing Surgical Treatment for Arthritis of the Distal Radioulnar Joint - Yayac, Michael; Padua, Fortunato G.; Banner, Lauren; Seigerman, Daniel A.; Beredjiklian, Pedro K.; Aita, Daren J.; Fletcher, Daniel (Journal of Wrist Surgery, 2020)
Objective Surgical treatment options for distal radioulnar joint (DRUJ) arthritis include distal ulnar resection (DUR), DRUJ arthrodesis, and ulnar head replacement. Ulnar convergence leading to persistent pain and clicking is a relatively common complication of complete DUR and DRUJ arthrodesis with distal ulnar segment resection (DRUJA). This led to the development of the distal ulna hemiresection (DUHR) and distal ulnar stump stabilization techniques to reduce the risk of this complication. Patients may experience incomplete relief of pain and limited range of motion (ROM) with these procedures. We hypothesized that there would be no differences in outcomes between the treatment groups, but patients undergoing DUHR, tendon interposition, or distal ulnar stump stabilization would be at lower risk of complications.Methods Records were retrospectively reviewed for 121 patients undergoing DRUJ procedures between 2000 and 2018 at a single institution to collect patient demographics, surgical details, preoperative diagnosis, and outcomes including complications, revision procedures, ROM, pain, and swelling. Patients were grouped for analysis by procedure type: DUR (Darrach procedure), DUHR (Bowers procedure), and DRUJA (Sauve–Kapandji procedure). Continuous variables were compared using an analysis of variance test and categorical variables using the Freeman–Halton extension of the Fisher's exact test. A multivariate logistic regression analysis was performed to identify significant predictors of outcomes.Results Seventy-three patients underwent a DUR procedure, while 33 patients underwent a DUHR procedure and 11 underwent a DRUJA procedure. Mean follow-up was 70.6 months. Patients undergoing DRUJA were significantly younger than those undergoing DUR or DUHR procedure (42.4 vs. 60.0 vs. 62.1, p < 0.001). No significant differences between groups were demonstrated in measured outcomes. Posttraumatic arthritis was the most common preoperative diagnosis (43.4%). Persistent pain was the most common negative outcome (25.6%) followed by limited ROM (19.7%). Five patients (4.3%) suffered postoperative complications, most common being rupture of extensor tendons. Five patients (4.3%) underwent revision procedures. Body mass index (BMI) was a significant predictor of persistent pain (odds ratio = 1.09, p = 0.031).Conclusion The results of our study suggest that outcomes are equivalent between the three distinct treatment groups. Despite the potential benefits, hemiresection, tendon interposition, and distal stump stabilization had no significant effect on outcomes in this study. More than a quarter (25.6%) of patients undergoing DRUJ procedures experience persistent pain postoperatively, while one-fifth (19.7%) experienced limited ROM. Patients with higher BMI are at a significantly greater risk of experiencing persistent postoperative pain.Level of Evidence This is a Level III, retrospective comparative study.
Keywords: distal radioulnar joint; DRUJ trauma; Suave–Kapandji; Darrach; Bowers